2020
DOI: 10.1038/s41439-020-00110-0
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese boy with NAA10-related syndrome and hypertrophic cardiomyopathy

Abstract: NAA10-related syndrome is an extremely rare X-chromosomal disorder, the symptoms of which include intellectual disability (ID), ocular anomalies, or congenital heart diseases, such as hypertrophic cardiomyopathy (HCM). Here, we describe a 4-year-old Japanese male patient who exhibited mild ID, HCM, and specific facial features. A hemizygous mutation (NM_003491.3: c.455_458del, p. Thr152Argfs*6) in exon 7 of NAA10 was detected. We recommend that patients undergo precise medical follow-up considering the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…She also has stigmatism in her left eye, along with myopia and possible cortical visual impairment. Individual 54 (a male) with p.Thr152Argfs*6 in NAA10 also has microphthalmia, similarly to a previously published case (Cheng et al 2019), whereas the male in Japan did not have microphthalmia (Shishido et al 2020). Individual 55 has p.Glu181Alafs*67 and does not have microphthalmia, indicating that even frameshift variants toward the C-terminus of NAA10 can have quite variable outcomes.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…She also has stigmatism in her left eye, along with myopia and possible cortical visual impairment. Individual 54 (a male) with p.Thr152Argfs*6 in NAA10 also has microphthalmia, similarly to a previously published case (Cheng et al 2019), whereas the male in Japan did not have microphthalmia (Shishido et al 2020). Individual 55 has p.Glu181Alafs*67 and does not have microphthalmia, indicating that even frameshift variants toward the C-terminus of NAA10 can have quite variable outcomes.…”
Section: Resultssupporting
confidence: 81%
“…One child (Individual 1) was found to have two novel variants on the same sequencing Most of the NAA10 variants are de novo, with the exception of p.Tyr43Ser in a previously reported family (Casey et al 2015), p.Ile72Thr in two families (one of which, Individual 8, was previously reported (Støve et al 2018;Cheng et al 2019) and Individual 54 with frameshift variant p.Thr152Argfs*6, with this same p.Thr152Argfs*6 variant being reported in two other cases (Shishido et al 2020;Cheng et al 2019).…”
Section: Naa10 and Naa15 Variantsmentioning
confidence: 84%
“…Compared to missense variants, alterations in the NAA10 gene which result in a (partial) loss of protein function due to reduced mRNA levels can lead to syndromic microphthalmia/anophthalmia in boys (Esmailpour et al, 2014 ; Johnston et al, 2019 ; Shishido et al, 2020 ). Complete loss‐of‐function of NAA10, however, is thought to be lethal in males (Popp et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence demonstrated that KCNJ2 [128], TLR4 [129], CYP2D6 [130], TLR2 [129], SNX10 [131], SIRT1 [132], PF4 [133], PCYT2 [134] and LGALS3 [135] were altered expression in atrial fibrillation. Studies had shown that KCNJ2 [136], ARG1 [137], TLR4 [138], IFIH1 [139], FBN2 [140], PDK4 [141], TLR8 [142], PDGFC (platelet derived growth factor C) [143], FNIP1 [144], TLR2 [145], PTPN11 [146], LATS2 [147], GCH1 [148], ARFGEF2 [149], CA2 [150], PTPRC (protein tyrosine phosphatase receptor type C) [151], CCR2 [152], GAB1 [153], VEGFA (vascular endothelial growth factor A) [154], UBR1 [155], PHLPP1 [156], MTM1 [157], FMR1 [158], SIRT1 [159], NOD2 [160], MYOF (myoferlin) [161], OSBPL11 [162], ZBTB11 [121], UTRN (utrophin) [163], ZNF593 [164], CCR7 [165], PRDX2 [166], BIN1 [167], NFIC (nuclear factor I C) [168], TCF4 [169], PPP1R13L [124], NDUFB11 [170], TAX1BP3 [171], TRPM4 [172], NMRAL1 [173], LGALS3 [126] and NAA10 [174] were associated with cardiomyopathy. CD274 [175], CEACAM1 [176], STAT1 [177], ARG1 [178], TLR4 [179], LRRK2 [180], ABCA1 [181], IFIH1 [182], TLR5 [183], PTGS2 [184], CYP2D6 [185], RNF213 [186], C9ORF72 [187], JAK2 [188], TLR8 [189], NOTCH2 [190], PDGFC (platelet derived growth factor C) [191], TLR2 [192], PRKAB2 [193], HDAC9 [194], NCOA4 [195], LATS2 [196], DICER1 […”
Section: Discussionmentioning
confidence: 99%